Cosmic Apprentice : Dispatches from the Edges of Science - Sagan, Dorion, 1959- (Book collections on Project MUSE., 2013)
Refreshingly nonconformist and polemically incisive, this book challenges readers to reject both dogma and cliche and instead recover the intellectual adventurousness that should - and can once again - animate both science and philosophy. Informed by a countercultural sensibility, a deep engagement with speculative thought, and a hardheaded scientific skepticism, it advances controversial positions on such seemingly sacrosanct subjects as evolution and entropy.